2005
DOI: 10.1007/s11104-004-8128-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biochemical quality on C and N mineralisation from a broad variety of plant materials in soil

Abstract: We studied C and N mineralisation patterns from a large number of plant materials (76 samples, covering 37 species and several plant parts), and quantified how these patterns related to biological origin and selected indicators of chemical composition. We determined C and N contents of whole plant material, in water soluble material and in fractions (neutral detergent soluble material, cellulose, hemicellulose and lignin) obtained by stepwise chemical digestion (modified van Soest method). Plant materials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
134
2
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(171 citation statements)
references
References 38 publications
20
134
2
15
Order By: Relevance
“…Using this approach, mass loss, elemental composition, specific compounds, or isotopic signature have been monitored at specific sampling dates over periods of up to 3 years. Most of these studies show that N-rich and water-soluble compounds as well as celluloses are rapidly degraded (Williams and Gray, 1974;Nelson et al, 1994;Kerem et al, 1999;Marschner and Noble, 2000;Webster et al, 2000;Jensen et al, 2005), while lignin and other polyphenols tend to accumulate during the initial stages of litter decomposition (Williams and Gray, 1974;Azam et al, 1985;Kalbitz et al, 2006). Since plant compounds are not uniformly labeled with 13 C, this parameter has also been used as a tool to identify compositional changes during litter decomposition (Schweizer et al, 1999).…”
Section: Decomposition and Incubation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, mass loss, elemental composition, specific compounds, or isotopic signature have been monitored at specific sampling dates over periods of up to 3 years. Most of these studies show that N-rich and water-soluble compounds as well as celluloses are rapidly degraded (Williams and Gray, 1974;Nelson et al, 1994;Kerem et al, 1999;Marschner and Noble, 2000;Webster et al, 2000;Jensen et al, 2005), while lignin and other polyphenols tend to accumulate during the initial stages of litter decomposition (Williams and Gray, 1974;Azam et al, 1985;Kalbitz et al, 2006). Since plant compounds are not uniformly labeled with 13 C, this parameter has also been used as a tool to identify compositional changes during litter decomposition (Schweizer et al, 1999).…”
Section: Decomposition and Incubation Experimentsmentioning
confidence: 99%
“…Early studies of litter decomposition showed that lignin content was inversely related to mass loss (Williams and Gray, 1974). However, several recent studies have shown, that a selective preservation of lignin appears to be only relevant during the early stages of litter decomposition and that later-on lignin degradation occurs at the same or even higher rate as the overall litter decomposition (Gleixner et al, 1999;Kerem et al, 1999;Jensen et al, 2005;Prescott, 2005;Kalbitz et al, 2006;Sollins et al, 2006). Recent studies using 13 C-CPMAS-NMR and pyrolysis techniques have confirmed that lignin is altered relatively quickly and does not appear to be stabilized in the long-term in any soil fraction (Baldock and Nelson, 2000;Gleixner et al, 2002;Kiem and Kögel-Knabner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…soil temperature and moisture) and intrinsic factors related to plant materials characteristics (i.e. lignin and cellulose content, total and soluble N content, C/N ratio; Jensen et al, 2005). In particular, the C/N ratio of the plant material, even if considered only an approximate guide to the likely net mineralisation, is often able to provide a valuable prediction of N mineralisation and can be effectively utilised in the current practice (Canali et al, 2011).…”
Section: The Role Of Asc Genotype and Mixtures Of Ascmentioning
confidence: 99%
“…However, some researchers have found that the pool of SON was of equal size to soluble inorganic N [76], and it became important to evaluate the SON content and its contribution during N mineralization. Some researchers reported that the initial net N mineralization rate from organic amendments was most closely correlated (r = 0.76) with the water-soluble N content, for a broad variety of plant materials in soil [52]. Water-soluble C and N pools have been hypothesized to play a central role in the transport and supply of C and N to microbial populations in soils and thus, the regulation of subsequent microbially mediated N transformations [24].…”
Section: Transformation Of Carbon and Nitrogen During Decompositionmentioning
confidence: 99%